Fens mapping for the Manti-La Sal National Forest - Smith, Gabrielle, author; Lemly, Joanna, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2017)
This report and associated dataset provide the MLSNF with a critical tool for conservation planning at both a local and Forest-wide scale. These data will be useful for the ongoing MLSNF biological assessment required by the 2012 Forest Planning Rule, but can also be used for individual management actions, such as planning for timber sales, grazing allotments, and trail maintenance. Wherever possible, the Forest should avoid direct disturbance to the fens mapped through this project, and should also strive to protect the watersheds surrounding high concentrations of fens, thereby protecting their water sources.
Fen mapping for the Manti-La Sal National Forest
Prepared for: Manti-La Sal National Forest.
April 2017.
Keywords: wetlands; fens; conservation; restoration